SYNTHESIS OF 1-ARYL-6,6-DIMETHYL-2-PHENYL-6,7-DIHYDRO-1H-INDOL-4(5H)-ONES BY TWO STEPS, IN A THREE-COMPONENT REACTION - Khalafy, Jabbar; Badparvar, Fahimeh; Marjani, Ahmad Poursattar (Journal of the Chilean Chemical Society, 2016)
An efficient method for the synthesis of 1-aryl-6,6-dimethyl-2-phenyl-6,7-dihydro-1H-indol-4(5H)-ones is achieved in two steps, using a three-component reaction of phenacyl bromide, dimedone and aniline derivatives in water-ethanol (1:1) under reflux conditions.